Deep roots: applying permaculture principles in order to mitigate flooding within the urban fabric of New Orleans - Schaap, Andrew (Kansas State University, 2010)
Urbanization has lead to environmental degradation in most of the world’s great cities. With the degradation of natural systems comes a reliance on man-made and engineered systems to perform functions vital to cities such as water treatment, the filtering of pollutants, flood mitigation, temperature control, and erosion prevention; functions formerly performed by natural systems. Relying on man-made operations to perform essential services comes at a cost, both in terms of monetary costs and in the resources needed to construct and operate them. New Orleans is a prime example of a city that has greatly altered the ecosystems that formerly existed on the site and has had to rely on human engineering for its survival. Instead of the mosaic of freshwater marshes, wooded swamps, wet meadows, and bottomland forests that once comprised New Orleans and allowed for the diffusion, evaporation, and infiltration of floodwater; present day New Orleans has had to rely on a system of levees and pumps to keep the City dry. These pumps and levees have allowed New Orleans to expand and prosper but failures in the flood control system have also lead to great disasters, Hurricane Katrina and the related flood in 2004 being the latest. Implementing permaculture designs to New Orleans will buffer the City from the effects of hurricanes and flooding and decrease its reliance on city services. These permaculture designs recreate key elements of the natural systems that formerly existed in New Orleans and attempt to again create spaces in the City were stormwater can safely be detained without damaging property and that allow the stormwater to infiltrate into the soil. At the same time these permaculture designs would enhance the character and uniqueness that makes New Orleans one of the world’s great cities.
Keywords: Landscape Architecture; Permaculture; New Orleans; Flooding; Stormwater; Wetlands; Landscape Architecture (0390)